HUBUNGAN PERSEN PENUTUPAN LAMUN DAN STRUKTUR KOMUNITAS ECHINODERMATA DI PULAU RA’AS - Alex Purnomo; Wahyu Andy Nugraha (Jurnal Kelautan, 2020)
ABSTRACTSeagrass beds are one of the ecosystems that support a variety of life in the sea. Various types of biota live around seagrass beds, one of which is Echinodermata. Echinodermata has a role as a detritus eater in seagrass plants. The association of Echinodermata and seagrass species can be used to see the suitability of a habitat for the existence of species that live in seagrass ecosystems. The purpose of this study was to determine the associations of Echinoderms and Seagrasses on Ra'as Island, Brakas Village, Telangoh Tengah Hamlet, Sumenep Regency, East Java. This research was conducted in November-December 2018. The method used is the quadratic method placed on the transect line with the size of each quadrant of 1x1 m. The association of Echinodermata and Seagrass relationships between Echinoderms and Seagrasses was analyzed by simple linear regression. The results showed that there were 4 species of Echinoderms and 3 species of seagrass. Diversity, uniformity and dominance of Echinoderms at each is low. The association of Echinoderms and Seagrasses showed that seagrass results and Echinodermata did not have a significant relationship. The influencing factor is that most Echinoderms found are Echinoderms, which occupy coral reef ecosystems such as Diadema sitosum, which is most often found at each station.Keywords: Seagrass, Community Structure, Relationship to Seagrasses and Echinoderms, Ra'as IslandABSTRAKPadang lamun adalah salah satu ekosistem yang menyangga berbagai kehidupan di laut. Berbagai macam biota hidup disekitar padang lamun salah satunya adalah Echinodermata. Echinodermata memiliki peranan sebagai pemakan detritus pada tumbuhan lamun. Asosiasi spesies Echinodermata dan lamun dapat digunakan untuk melihat tingkat kesesuaian suatu habitat bagi keberadaan spesies yang hidup pada ekosistem padang lamun. Tujuan penelitian ini untuk mengetahui asosiasi Echinodermata dan lamun di Pulau Ra’as, Desa Brakas, Dusun Telangoh Tengah, Kabupaten Sumenep, Jawa Timur. Penelitian ini dilaksanakan pada bulan November-Desember 2018.  Metode yang digunakan metode kuadrat yang diletakkan pada garis transek dengan ukuran tiap kuadran 1x1 m. Asosiasi Echinodermata dan lamun hubungan Echinodermata dan lamun dianalisis dengan regresi linier sederhana. Hasil penelitian menunjukkan terdapat 4 spesies Echinodermata dan 3 spesies lamun. Keanekaragaman, keseragaman, dan dominasi Echinodermata pada setiap stasiun adalah rendah. Asosiasi Echinodermata dan lamun menunjukkan hasil tidak memiliki hubungan yang signifikan. Faktor yang mempengaruhi adalah kebanyakan Echinodermata yang di temukan adalah Echinodermata yang menempati ekosistem terumbu karang seperti Diadema sitosum yang paling sering ditemukan pada setiap stasiun.Kata Kunci: Lamun, Struktur Komunitas, Hubungan Lamun dan Echinodermata, Pulau Ra’as